1986
DOI: 10.1099/0022-1317-67-7-1449
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Region X of Hepatitis B Virus Genome in Human Primary Hepatocellular Carcinomas Propagated in Nude Mice

Abstract: SUMMARYTissues of human primary hepatocellular carcinoma (PHC) from six patients infected with hepatitis B virus (HBV) were propagated in nude mice, as well as a strain of hepatitis B surface antigen-positive PHC (PLC/PRF/5). Integration of viral DNA into chromosomal DNA of tumour cells was evaluated by the capacity to hybridize with radiolabelled DNA probes, each representing fundamental parts of the HBV genome, that is S and C genes and regions pre-S and X. All PHC cells possessed region X integrated in thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
1

Year Published

1989
1989
2000
2000

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 15 publications
0
22
0
1
Order By: Relevance
“…Alternatively, it has been suggested that production of novel class III transcripts may play a role during transformation of rodent cells by SV40 or by chemical carcinogens (Singh et al, 1985;Carey et al, 1986), as well as during active proliferation (Edwards et al, 1985). HBV infected tissues are generally thought to be stimulated to divide, and many HCC tumors derived from infected livers contain integrated copies of at least part of the X-gene (Shaul et al, 1984;Miyaki et al, 1986;Nagaya et al, 1987). Thus, it is tempting to speculate that activation of certain class III genes might be involved in proliferation of infected cells or perhaps carcinogenesis by HBV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, it has been suggested that production of novel class III transcripts may play a role during transformation of rodent cells by SV40 or by chemical carcinogens (Singh et al, 1985;Carey et al, 1986), as well as during active proliferation (Edwards et al, 1985). HBV infected tissues are generally thought to be stimulated to divide, and many HCC tumors derived from infected livers contain integrated copies of at least part of the X-gene (Shaul et al, 1984;Miyaki et al, 1986;Nagaya et al, 1987). Thus, it is tempting to speculate that activation of certain class III genes might be involved in proliferation of infected cells or perhaps carcinogenesis by HBV.…”
Section: Discussionmentioning
confidence: 99%
“…There is also evidence that the X-gene is expressed during at least some stage of HBV infection, since many individuals produce antibodies to the X-protein (Kay et al, 1985;Moriarity et al, 1985;Elfassi et al, 1986;Meyers et al, 1986;Persing et al, 1986). At least part of the X-ORF is retained in many tumors (Shaul et al, 1984;Miyaki et al, 1986;Nagaya et al, 1987), and in one example, trans-activation ability was maintained (Wollersheim et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…78,80,81 In this study, we observed a close statistical correlation between expression of HBx and existence of HBsAg in HCC-bearing liver, which may reflect the frequent preservation of the X gene together with the PreS2/S1 region during the integration of HBV DNA into cellular genomic DNA and the following rearrangements. [65][66][67][68] However, their distribution patterns were differ- ent. Our results demonstrated that the expression of HBx, among the three HBV antigens examined, was preferentially maintained through the multistage process from foci and nodules of altered hepatocytes, for which a preneoplastic nature has been demonstrated, 54,57 to HCC.…”
Section: Discussionmentioning
confidence: 99%
“…[65][66][67][68] HBx variants expressed from the chromosomally integrated mutants may also contribute to different HBx distribution patterns and expression levels, particularly in the neoplastic lesions. Combined use of several antibodies recognizing different epitopes, as in this study, should greatly increase the possibility to detect HBx in the tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation